Inflation Hedging for Long-Term Investors - Roache, Shaun; Attie, Alexander (Washington, D.C. : International Monetary Fund, 2009)
Long-term investors face a common problem-how to maintain the purchasing power of their assets over time and achieve a level of real returns consistent with their investment objectives. While inflation-linked bonds and derivatives have been developed to hedge the effects of inflation, their limited supply and liquidity lead many investors to continue to rely on the indirect hedging properties of traditional asset classes. In this paper, we assess these properties over different time horizons, in the context of a diversified portfolio. Using a vector error correction model, we find that effective short-run hedges, such as commodities, may not work over longer horizons and that tactical asset allocation could enhance investment returns following inflation surprises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet